A study on the computerized revenue collection system of local authority: A case of Perlis, Kedah and Penang - Abdul Talib, Yurita Yakimin; Mohd Lazim, Marlina; Ismail, Mohamad Sharofi (Universiti Utara Malaysia, 2005)
This survey identifies the extent of computerized revenue collection system use among the local authorities in the northern region of Peninsular Malaysia. Survey questionnaires and interviews were gathered from 14 local authorities located in Perlis, Kedah and Penang. The study shows a high adoption rate (100%) among the respondents, due to the awareness of importance of automated system in data processing. However, the extent of use of the adopted system is still low due to the difficulty in selecting suitable software, lack of expertise and experience, cost constraints, attitude problems and lack of training. Some recommendations have been made to improve the existing scenario. They include provide training and consultation to the users on latest advancement of technology in accounting, develop specific software for revenue collection and government can also support the local authorities by providing financial assistance and expertise in technology. The study concludes that the local authorities in the northern region are not yet prepared to implement e-collection to the public.